Kajian Senyawa Aktif Tanaman Obat sebagai Agen Antihipertensi pada Kehamilan - Nadya Syarifatul Fajriyah; Suharno Zen; Ilham Fathurrahman; Miftahuz Zakiyah (Jurnal Sains Biomedis, 2025)
Hypertension during pregnancy is a major complication that poses significant risks to both maternal and fetal health. While pharmacological treatments are commonly used, their application is often limited due to potential adverse effects on fetal development, thereby necessitating safer alternative therapies, such as the use of medicinal plants. This study aims to examine the active compounds found in medicinal plants with antihypertensive potential and to evaluate their mechanisms of action within the context of pregnancy. A descriptive qualitative literature review was conducted by analyzing scientific articles published between 2010 and 2025 through databases such as PubMed, ScienceDirect, and Google Scholar. The review identified several plants, including Moringa oleifera, Zingiber officinale, Annona muricata, and Cymbopogon citratus, which contain bioactive compounds such as flavonoids, gingerol, acetogenins, and citral. These compounds contribute to blood pressure reduction through mechanisms such as vasodilation, antioxidant activity, diuretic effects, and inhibition of the angiotensin-converting enzyme (ACE). The findings suggest that these active compounds from medicinal plants have promising potential as safe antihypertensive agents during pregnancy; however, further large-scale clinical trials are necessary to confirm their long-term safety and efficacy